Ordered colloidal clusters constructed by nanocrystals with valence for efficient CO2 photoreduction - Nai, Jianwei (2020)
The ability to construct discrete colloidal clusters (CCs) as complex as molecular clusters is limited due to the lack of available colloidal building blocks and specific directional bonds. Here, we explore a strategy to organize anisotropic Prussian blue analog nanocrystals (NCs) toward CCs with open and highly ordered structures, experimentally realizing colloidal analogs to zeolitic clathrate structures. The directional interactions are derived from either crystallographic or morphological anisotropy of the NCs and achieved by the interplay of epitaxial growth, oriented attachment, and local packing. We attribute these interparticle interactions to enthalpic and entropic valences that imitate hybridized atomic orbitals of sp3d2 octahedron and sp3d3f cube. Benefiting from the ordered multilevel porous structures, the obtained CCs exhibit greatly enhanced catalytic activity for CO2 photoreduction. Our work offers some fundamental insights into directional bonding among NCs and opens an avenue that promises access to unique CCs with unprecedented structures and applications.